2007
DOI: 10.1186/1471-2458-7-155
|View full text |Cite
|
Sign up to set email alerts
|

The association between weekly hours of physical activity and mental health: A three-year follow-up study of 15–16-year-old students in the city of Oslo, Norway

Abstract: Background: Mental health problems are a worldwide public health burden. The literature concerning the mental health benefits from physical activity among adults has grown. Adolescents are less studied, and especially longitudinal studies are lacking. This paper investigates the associations between weekly hours of physical activity at age 15-16 and mental health three years later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
103
2
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 44 publications
16
103
2
8
Order By: Relevance
“…The associations were observed both before and after adjusting for weekly exercise, healthy diet, and number of friends. Our findings are in accordance with those of previous studies, which have reported emotional problems and peer problems to be inversely associated with physical activity in adolescents (10). The relationship between participation in either noncompetitive or competitive sports and conduct or hyperactivity problems was less strong in the present study, but it was significant.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The associations were observed both before and after adjusting for weekly exercise, healthy diet, and number of friends. Our findings are in accordance with those of previous studies, which have reported emotional problems and peer problems to be inversely associated with physical activity in adolescents (10). The relationship between participation in either noncompetitive or competitive sports and conduct or hyperactivity problems was less strong in the present study, but it was significant.…”
Section: Discussionsupporting
confidence: 79%
“…A study conducted in Iceland revealed that adolescents who often practiced sports had a more positive body image and were more likely to report a healthy mental condition (9). Further, emotional problems and peer problems have been found to be inversely associated with physical activity in adolescents (10).…”
Section: Introductionmentioning
confidence: 99%
“…The results are in line with previous findings showing that boys are more physically active than girls, but contradict previous findings showing that the amount of physical activity seems to decline with age both among boys and girls during adolescence [14,15]. Physical activity is a behavior influenced by complex intrapersonal, social and environmental factors, and there are a number of potential explanations for the observed gender differences found on LVPA.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies have shown that physical activity has a range of positive psychological and physiological health benefits for adolescents and is an important component of a healthy lifestyle [9][10][11][12][13].However,the frequency of physical activity and exercise seem to decrease from childhood to adolescence, especially in girls [14,15]. Cross-sectional and longitudinal studies have stated that physical activity is beneficial in relation to depression in adolescents [9,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…3 studies had a primary focus on motor activity alongside other variables rather than measuring physical activity Walther et al, 2011;Walther, Koschorke, Horn, & Strik, 2009a,b, Walther et al, 2009b 11 studies that reported physical activity without a specific SRQ Arango et al, 2008;Bobes et al, 2010a,b;Buhagiar et al, 2011;Chwastiak, Rosenheck, Lewis, & Kazis, 2011;Farnam, Zipple, Tyrrell, & Chittinanda, 1999;Guzik & Wirshing, 2007;Hutchinson, 2005;Menza et al, 2004;Smith et al, 2007;ten Have, de Graaf, & Monshouwer, 2011;Vreeland et al, 2003. 6 studies did not include individuals with a diagnosis of SMI Koivukangas et al, 2010;Kopp et al, 2011;Sagatun, Søgaard 1 This includes the duplication of studies across groups e.g., some studies measure physical activity more than one way. Structure and Items: 5 broad categories of activity are identified with the following number of items in each: work (n = 12 items), Yard work (n = 4 items), care taking (n = 2 items), Exercise (n = 6 items).…”
Section: The Identification Of the Different Outcome Measures Usedmentioning
confidence: 99%